2016
DOI: 10.1186/s12936-016-1595-9
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium vivax multidrug resistance-1 gene polymorphism in French Guiana

Abstract: Background Plasmodium vivax malaria is a major public health problem in French Guiana. Some cases of resistance to chloroquine, the first-line treatment used against P. vivax malaria, have been described in the Brazilian Amazon region. The aim of this study is to investigate a possible dispersion of chloroquine-resistant P. vivax isolates in French Guiana. The genotype, polymorphism and copy number variation, of the P. vivax multidrug resistance gene-1 (pvmdr1) have been previously associated with modification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 45 publications
0
21
0
Order By: Relevance
“…Increased pvmdr1 copy number was associated with reduced sensitivity to MFQ in some studies [31][32][33]73]. Like in P. falciparum [74], pvmdr1 amplification was also rare at the China-Myanmar border and only detected in three isolates (3/64).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Increased pvmdr1 copy number was associated with reduced sensitivity to MFQ in some studies [31][32][33]73]. Like in P. falciparum [74], pvmdr1 amplification was also rare at the China-Myanmar border and only detected in three isolates (3/64).…”
Section: Discussionmentioning
confidence: 91%
“…Whereas some studies reported the association of the pvmdr1 substitutions Y976F with CQR P. vivax in vitro [27], others did not find such an association [28][29][30]. Some studies have found that an increase in pvmdr1 gene copy number was correlated with increased susceptibility to CQ, but perhaps reduced susceptibility to MFQ [31][32][33]. In a study from Brazil, higher expression levels of pvcrt-o and pvmdr1 were shown to confer CQ resistance in P. vivax [34].…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 97%
See 1 more Smart Citation
“…[16][17][18][19] More recent studies show the presence of P. vivax isolates harboring CQ-resistant mutations in French Guiana and Brazil. 20,21 Reported cases of TF with CQ alone in South America suggest that it is necessary to monitor the clinical and parasitological response to the drug because of a possible unrecognized emergence of resistant P. vivax strains in Colombia, although the extent of the threat to national malaria control efforts remains to be determined. In Colombia, the initial studies between 1998 and 2011 found a 100% ACPR to CQ alone in patients with malaria vivax monoinfection [22][23][24][25][26] ; one study reported an 11% rate of TFs in 2001, defined by the authors as "clinical drug resistance" 27 ; and one study addressed P. vivax in vitro susceptibility to various drug regimens between 2010 and 2012.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies in Southeast Asia have shown that P. vivax isolates with pvmdr1 ( P. vivax multidrug-resistant gene 1) gene amplification were characterized by increased susceptibility to chloroquine but decreased susceptibility to mefloquine (Imwong et al, 2008 ; Suwanarusk et al, 2008 ). Nevertheless, the role of pvmdr1 in conferring resistance to chloroquine is still elusive and controversial (Faway et al, 2016 ). Although number of pvmdr1 gene copies correlated with mefloquine use history, in vivo data showing a direct relationship between mefloquine resistance and pvmdr1 gene amplification form mefloquine-treated patients are needed (Khim et al, 2014 ).…”
mentioning
confidence: 99%